DYNAMICS OF AGRICULTURAL EXTENSION SERVICES IN PAKISTAN: A HISTORY OF NATIONAL PERFORMANCE - S. Ashraf; Z. Y. Hassan; I. Ashraf (Journal of Animal and Plant Sciences, 2019)
Extension Advisory Services (EAS) are under criticism in various countries and Pakistan is one of them. In this mixed-method research study, various reasons for this criticism are explored. This study followed a supportive model of organizational behaviour as a conceptual model and summarized results through secondary and primary data sources. Scholarly articles and grey literature during 1952-2018 was critically examined followed by a discussion with 10 experts who had been a part of extension programs in the past to evaluate various extension programs implemented in Pakistan. 180 purposively selected respondents from Extension Field Staff (EFS) were interviewed qualitatively to underpin factors affecting their performance. Results summarized that EAS in Pakistan is perceived as ineffective and failed to meet the farmer’sneeds. Since 1952 numerous programs were implemented but abolished one after the other without any significant impact. Derisory coordination, departmental rivalries, political involvement, ignored participation of local elite in planning, misuse of funds and financial obstructions caused failure of programs. At present, working Field Staff is facing the same challenges like no service structure, lack of mobility means, no incentives and rewards, inappropriate offices, involvement in irrelevant duties, a large ratio of extension staff to farmers and weak inter- and intra-departmental communication and coordination gap turning the services ineffective. This implies that since the inception of EAS nothing is changed and EFS is confronted with inherited problems and confused roles to play.
Keywords: extension services; evaluation; policy; coordination; model